Canonical Correlation Analysis in the Study of Cerebral and Peripheral Haemodynamics Interrelations with Systemic Variables in Neonates Supported on ECMO (2012)
Neonates supported on extracorporeal membrane oxygenation (ECMO) are at high risk of brain injury due to haemodynamic instability. In order to monitor cerebral and peripheral (muscle) haemodynamic and oxygenation changes in this population we used a dual-channel near-infrared spectroscopy (NIRS) system. In addition, to assess interrelations between NIRS and systemic variables, collected simultaneously, canonical correlation analysis (CCA) was employed. CCA can quantify the relationship between a set of variables and assess levels of dependency. In four out of five patients, systemic variables were found to be less inter-related with cerebral rather than peripheral NIRS measurements. Moreover, during ECMO flow manipulations, we found that the interrelation between the systemic and the NIRS cerebral/peripheral variables changed. The CCA method presented here can be used to assess differences between NIRS cerebral and NIRS peripheral responses due to systemic variations which may be indicative of physiological differences in the mechanisms that regulate oxygenation and/or haemodynamics of the brain and the muscle.